Recycling behaviour of Malaysian urban households and upcycling prospects / Carol Boon-Chui Teo - Teo, Carol Boon-Chui (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
Households remain the main generator of municipal solid waste in Malaysia. Malaysians produce an average of 30,000 tons of waste per day and only 5 per cent of it is recycled. Malaysian urbanites throw away waste more than normal. The solid waste generated continues to be a costly affair with about two-thirds of the local councils' total collected annual assessment fees being spent to manage waste. Yet at the same time, Malaysia's waste recycling rate is way below the average levels. Hence the perennial question remains as to why Malaysian households are not recycling or recycling enough. This study investigates recycling behavior of urban households in a green city. Methodology utilized survey questionnaire approach to 100 households to determine residents' willingness to participate in recycling activities. Results revealed proactive and reactive behaviors indicating two distinct recycling groups. Analysis generated factors of convenience of recycling facilities and services, environmental involvement recycling benefits and habitual recycling in the two groups. Willingness to recycle differed across the two groups. Recycling benefits and convenience to recycling facilities significantly influenced the behavior of proactive group while only habitual recycling was significant for the reactive group. Findings had implications on policy making and implementation of recycling programs. Upcycling prospects highlighted proactive roles of households to convert useless wastes into quality and marketable products to benefit the environment.